The Perception of Rhizosphere Bacterial Communication Signals Leads to Transcriptome Reprogramming in Lysobacter capsici AZ78, a Plant Beneficial Bacterium - Bejarano, Ana; Perazzolli, Michele; Pertot, Ilaria; Puopolo, Gerardo (Frontiers in Microbiology, 2021)
The rhizosphere is a dynamic region governed by complex microbial interactions where diffusible communication signals produced by bacteria continuously shape the gene expression patterns of individual species and regulate fundamental traits for adaptation to the rhizosphere environment. Lysobacter spp. are common bacterial inhabitants of the rhizosphere and have been frequently associated to soil disease suppressiveness. However, little is known about their ecology and how diffusible communication signals might affect their behaviour in the rhizosphere. To shed light on the aspects determining rhizosphere competence and functioning of Lysobacter spp., we carried out a functional and transcriptome analysis on the plant beneficial bacterium L. capsici AZ78 (AZ78) grown in presence of most common diffusible communication signals released by rhizosphere bacteria. Mining the genome of AZ78 and other Lysobacter spp. showed that Lysobacter spp. share genes involved in the production and perception of diffusible signal factors, indole, diffusible factors, and N-acyl-homoserine lactones. Most of the tested diffusible communication signals (i.e., indole and glyoxylic acid) influenced the ability of AZ78 to inhibit the growth of the phytopathogenic oomycete Pythium ultimum and the Gram-positive bacterium Rhodococcus fascians. Moreover, RNA-Seq analysis revealed that nearly a 21% of all genes in AZ78 genome were modulated by diffusible communication signals. 13-methyltetradecanoic acid, glyoxylic acid, and 2,3-butanedione positively influenced the expression of genes related to type IV pilus, which might enable AZ78 to rapidly colonize the rhizosphere. Moreover, glyoxylic acid and 2,3-butanedione down-regulated tRNA genes, possibly as a result of the elicitation of biological stress responses. On its behalf, indole down-regulated genes related to type IV pilus and the Heat Stable Antifungal Factor, which might result in impairment of twitching motility and antibiotic production in AZ78. These results show that diffusible communication signals may affect the ecology of Lysobacter spp. in the rhizosphere and suggest that diffusible communication signals might be used to foster rhizosphere colonization and functioning of plant beneficial bacteria belonging to the genus Lysobacter.